INCLUSIVE EDUCATION AS A RIGHTS-BASED APPROACH TO EDUCATING CHILDREN WITH DISABILITIES ("Conference on Universal Science Research 2023", 2026)
Inclusive education has emerged as a fundamental human rights-based approach to ensuring equitable access to quality education for children with disabilities. This study explores how inclusive education aligns with international human rights frameworks and evaluates its effectiveness in promoting participation, equality, and social integration.